2012 IEEE Fourth International Conference on Digital Game and Intelligent Toy Enhanced Learning 2012
DOI: 10.1109/digitel.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Tutor Learning Using a Teachable Agent that Asks the Student Tutor for Explanations

Abstract: We have built SimStudent, a computational model of learning, and applied it as a peer learner that allows students to learn by teaching. Using SimStudent, we study the effect of tutor learning. In this paper, we discuss an empirical classroom study where we evaluated whether asking students to provide explanations for their tutoring activities facilitates tutor learning -the self-explanation effect for tutor learning. The results showed that students in the self-explanation condition displayed the same amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…In the learning sciences, we see a parallel line of research about learning by mentoring [4,20]. Mentoring also involves providing assessment and instructions to others.…”
Section: Learning By Reviewingmentioning
confidence: 97%
See 1 more Smart Citation
“…In the learning sciences, we see a parallel line of research about learning by mentoring [4,20]. Mentoring also involves providing assessment and instructions to others.…”
Section: Learning By Reviewingmentioning
confidence: 97%
“…Theory from organization science (e.g., [36]) and learning science (e.g., [20]) would suggest that reviewing others' work can offer an opportunity to make a meaningful impact, induce a sense of responsibility, and improve motivation to master a task domain. This paper explores ancillary benefits-such as learning and performance increases-that peer reviewing can provide to the reviewers, not just to workers.…”
Section: Introductionmentioning
confidence: 99%
“…Yeah, let's do it! Some technically attractive efforts such as free-form explanation feedback (Popescu et al 2003), collaborative peer tutoring (Walker et al 2009), hand-written equation entry (Anthony et al 2005), and teachable agents (Matsuda et al 2012), have shown promise, but have not always produced clear demonstrations of improving student learning outcomes above and beyond those achieved by the existing tutor. Some approaches to supporting student metacognition and motivation, such as help-seeking (Roll et al 2014), sense-making on errors (Mathan and Koedinger 2003), or reducing gaming the system (Baker et al 2006) have been demonstrated to improve outcomes, but have not been incorporated, perhaps in part because of the cost of technical development.…”
Section: Q) What Was Particularly Challenging In Undertaking This Study?mentioning
confidence: 99%
“…A more detailed analysis of the 3 rd grade students' results showed that the game playing students' higher gains mainly derived from problems concerning conceptual understanding of the base-10 system (Pareto et al 2012). The version of SimStudent that enables learning-byteaching (Matsuda et al 2010) was used in a three-day classroom experimental study with 160 high school students (Matsuda et al 2012). The study compared two versions of the system: with and without a self-explanation module.…”
Section: Related Work: Learning By Teaching Systems and Teachable Agentsmentioning
confidence: 99%
“…Hence, the agent acts as "an ideal learner" and poses numerous deep, explanatory questions prompting the student-tutor to reflect on and explain her playing behaviour. Recently, Matsuda et al (2012) also added explanatory questions to their TA to prompt for self-explanation. The purpose of the teachable agent dialogue is three-fold; to challenge students to reflect on why they play as they do; to support transfer of tacit game playing knowledge to articulate language; and to provide a role model of questioning to imitate.…”
Section: Our Approachmentioning
confidence: 99%